Determinants of Murabahah Margin Income in Indonesian Islamic Commercial Banks, 2013–2018 - Gustianti, Rizky; Andriansyah, Yuli; Masuwd, Mowafg (Unisia, 2023)
This study investigates the factors influencing murabahah margin income in Islamic commercial banks in Indonesia from 2013 to 2018, focusing on the BI Rate, overhead costs, and third-party funds (Dana Pihak Ketiga abbreviated DPK in Bahasa Indonesia). It aims to explore how these variables, individually and collectively, affect murabahah pricing, which is critical for ensuring competitiveness and adherence to Sharia principles in Islamic finance. A quantitative approach was employed, utilizing secondary data from quarterly financial reports of Islamic banks. Multiple linear regression analysis, complemented by classical assumption tests, was used to evaluate the relationships between the independent variables and murabahah margin income. The analysis ensures robust insights into the financial dynamics of Islamic banking. The findings reveal that overhead costs significantly and positively influence murabahah margin income, underscoring the role of operational efficiency in pricing. While the BI Rate demonstrated a positive association with murabahah margins, its effect was statistically insignificant, highlighting the need for alternative Sharia-compliant benchmarks. DPK exhibited a negative but insignificant relationship, suggesting that its liquidity impact on murabahah margins may be indirect and moderated by other factors. The combined analysis showed that these variables significantly influence murabahah margins collectively, with overhead costs being the most dominant determinant. These results emphasize the interplay between macroeconomic indicators and operational strategies in murabahah pricing. They highlight the need for operational efficiency, ethical benchmarks, and innovative deposit mobilization strategies. This study contributes to the broader discourse on Islamic finance, offering actionable insights for improving financial sustainability and aligning practices with Sharia principles.